2018
DOI: 10.1016/j.biomaterials.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Cellular toxicity of silicon carbide nanomaterials as a function of morphology

Abstract: Silicon carbide has been shown to be biocompatible and is used as a coating material for implanted medical devices to prevent biofilms. Silicon carbide nanomaterials are also promising in cell tracking due to their stable and strong luminescence, but more comprehensive studies of this material on the nanoscale are needed. Here, we studied the toxicity of silicon carbide nanomaterials on human mesenchymal stem cells in terms of metabolism, viability, adhesion, proliferation, migration, oxidative stress, and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…On the contrary, more studies suggest that 1D nanostructures have a certain level of impact on cellular behavior, including cell viability, elongation, and differentiation [93]. For instance, Chen et al reported a study on the toxicity of silicon carbide (SiC) nanowires, as shown in Figure 4B, and nanospheres on human mesenchymal stem cells (hMSCs) and cancer cells [94]. The impact of toxicity on metabolism, viability, proliferation, migration, oxidative stress, and differentiation potency were comprehensively examined.…”
Section: Recent Advances In Nanowire Biosensorsmentioning
confidence: 99%
“…On the contrary, more studies suggest that 1D nanostructures have a certain level of impact on cellular behavior, including cell viability, elongation, and differentiation [93]. For instance, Chen et al reported a study on the toxicity of silicon carbide (SiC) nanowires, as shown in Figure 4B, and nanospheres on human mesenchymal stem cells (hMSCs) and cancer cells [94]. The impact of toxicity on metabolism, viability, proliferation, migration, oxidative stress, and differentiation potency were comprehensively examined.…”
Section: Recent Advances In Nanowire Biosensorsmentioning
confidence: 99%
“…Botsoa et al showed there was no toxicity after the uptake of SiC nanoparticles by 3T3-L1 fibroblasts cells for one week [46]. However, the reported results are controversial because the cytotoxicity was also dose-dependent, morphology-dependent, and structure and surface property-dependent [47,48].The latest research demonstrated that SiC is a promising coating as dental material, which displayed adjustable color to match the dental shade guide used in clinic and wear resistance [49]. However, the oral environment could be a hostile to dental ceramic materials.…”
mentioning
confidence: 99%
“…Botsoa et al showed there was no toxicity after the uptake of SiC nanoparticles by 3T3-L1 fibroblasts cells for one week [46]. However, the reported results are controversial because the cytotoxicity was also dose-dependent, morphology-dependent, and structure and surface property-dependent [47,48].…”
mentioning
confidence: 99%
“…All samples were analyzed by flow cytometry (CytoFLEX S, Beckman Coulter, CA, USA). 26 This experimental protocol was verified by Southern Biotechnology Associates in the USA.…”
Section: Apoptosis Assaymentioning
confidence: 97%
“…Their livers were immediately excised and preserved at −80°C and would undergo messenger RNA (mRNA) analysis. 26…”
Section: Biointeraction Assay Using Flimmentioning
confidence: 99%